2021
DOI: 10.33002/nr2581.6853.040313
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Temporal Variation of Water Quality Parameters and the Trophic State Index in a Subtropical Water Reservoir of Bangladesh

Abstract: This study was conducted to determine the suitability of water quality for fisheries management in Kaptai Lake from February 2019 to January 2020. Results showed that the temperature, transparency, TDS, pH, DO, EC, alkalinity and hardness were 20.9 to 31.8°C, 17 to 303 cm, 40 to 105 mg/L, 6.82 to 7.96, 6.1 to 7.65 mg/L, 75.33 to 172.33 µS/cm, 37 to 83 mg/L and 35 to 190 mg/L, respectively. However, nutrients as NH3, NO3-, NO2-, PO43- and SO42- were 0.01 to 0.05, 0.03 to 2.21, 36 to 96, 0.01 to 0.04 and 0.3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The higher EC is attributed to the high degree of anthropogenic activities such as waste disposal and runoff. The St-1 and St-5 showed the highest and lowest TDS content in both seasons, respectively where TDS content was higher in post-monsoon than monsoon that supported by [23]. and the CV showed positive relationship between variables.…”
Section: Figurementioning
confidence: 66%
“…The higher EC is attributed to the high degree of anthropogenic activities such as waste disposal and runoff. The St-1 and St-5 showed the highest and lowest TDS content in both seasons, respectively where TDS content was higher in post-monsoon than monsoon that supported by [23]. and the CV showed positive relationship between variables.…”
Section: Figurementioning
confidence: 66%
“…The runoff from the attachment area contributed a lot of dissolved solids (Kumari et al, 2019). Transparency was recorded maximum in 1.85 ± 0.33 m in the pre‐monsoon season and 1.1 ± 0.5 m the monsoon season, which indicates the rapid increase in suspended matter (silt, clay and organic matter) and sediment from the catchment areas during the monsoon season resulting in rise in turbidity (Halder et al, 1990; Islam et al, 2021), and high values occurred during summer due to lack of rain, runoff and flood water as well as gradual settling of suspended particles (Saxena & Saksena, 2012). Rahman (1992) suggested that productive water bodies have a transparency of no more than 0.4 m. similar seasonal trends were found in the Tono reservoir (Akongyuure & Alhassan, 2021), Raipur reservoir (Saxena & Saksena, 2012) and Sardar Sarovar reservoir (Koushlesh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…in rise in turbidity (Halder et al, 1990;Islam et al, 2021), and high values occurred during summer due to lack of rain, runoff and flood water as well as gradual settling of suspended particles (Saxena & Saksena, 2012). Rahman (1992) suggested that productive water bodies have a transparency of no more than 0.4 m. similar seasonal trends were found in the Tono reservoir (Akongyuure & Alhassan, 2021), Raipur reservoir (Saxena & Saksena, 2012) and Sardar Sarovar reservoir (Koushlesh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%